The Digital Age of HADR: Harnessing Technology for Relief Operations - Major General Muniruzzaman, A. N. M. (Retd). (2017)
The advancement in technology has far reaching consequences for many sectors including Humanitarian Assistance and Disaster Relief [HADR]. Satellite and mobile technology has brought about revolutionary changes in the prospect of improving the speed and efficiency of HADR operations.